AN ANALYSIS ON THE ENGLISH TEACHER STRATEGIES IN TEACHING READING COMPREHENSION AT SMK NEGERI 2 TONDANO - Ovelia Uguy,; Hampp, Paula; Kumayas, Tirza (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
What were the research's problems, how did English teachers teach reading comprehension to vocational high school students in the first grade, and how did English teachers teach reading comprehension to vocational high school students in the first grade? is high-quality. The vocational high school for English teachers was the focus of this study. This study used an interview and a checklist for observation. The study's findings revealed that the teacher employed two strategies: QARs (question-answer relationships). Using the scaffolding strategy, students can come up with ideas that they can understand. The teacher can use QARs (question-answer relationships) until their students fully comprehend what they have been taught. After reading the given text, the teacher is able to determine how well the student understands the task at hand and can direct the students to focus more on the text and comprehend its content